(untitled) (Journal of Advanced Veterinary and Animal Research, 2017)
Objective: The aim of this study was to evaluate the growth response and feed utilization of Clarias gariepinus juveniles fed graded levels of boiled Senna obtusifolia seed meal as replacement for soybean meal. Materials and methods: Five isocaloric and isonitrogenous diets were formulated. The diest were- control diet (with 0% inclusion level boiled S. obtusifolia seed meal i.e., 100% soybean meal),25%, 50%, 75% and 100% inclusion level (total replacement of soya bean meal). The feeds were fed to C. gariepinus juveniles at 5% of their body weight for 84 days in an indoor partial flow through system. Weight and standard length of C. gariepinus juveniles were taken every fortnight and water quality parameters were monitored weekly. Results: Experimental fish fed diets with 0 and 25% inclusion level of boiled S. obtusifolia seed meal gave the best results in terms of Mean Weight Gain (MWG) (20.22 and 19.79 g, respectively), Specific Growth Rate (1.82 and 1.83 respectively), Protein Efficiency Ratio (2.75 and 2.00, respectively) and the Lowest Feed Conversion Ratio (1.29 and 1.39 respectively). The lowest growth and feed utilization were observed in fish fed 100% inclusion level. The weight gain of fish decreased with increase in replacement level above 25%. There was no significant difference between control diet 0 and 25% inclusion level(P?0.05). Conclusion: Boiled S. obtusifolia seed meal is a nutritive source of plant protein and a good replacement for soybean meal at 25% inclusion level of boiled S. obtusifolia seed meal in formulating catfish feed for C. gariepinus juveniles without any deleterious effect. http://doi.org/10.5455/javar.2016.c17